Analysis of Value Added Tax Accounting Treatment at PT Daya Anugrah Mandiri Airmadidi Branch - ANTOW, Angelica; GAMALIEL, Hendrik; WANGKAR, Anneke (Journal of Governance, Taxation and Auditing, 2023)
Value Added Tax (VAT) is a levy imposed on every sale and purchase transaction of goods and services carried out by individual taxpayers or business entities that have received the status of a Taxable Entrepreneur (PKP). The last amendment to the VAT Law is in Law Number 7 of 2021 concerning the Harmonization of Tax Regulations (UU HPP). PT Daya Anugrah Mandiri or better known as Daya Motor is a subsidiary of the Daya Group engaged in the retail sector of Honda motorcycles. Every purchase and sale of motorbikes carried out by PT Daya Anugrah Mandiri Airmadidi Branch is inseparable from the imposition of Value Added Tax (PPN). The purpose of this study is to find out how the VAT accounting treatment is at PT Daya Anugrah Mandiri Airmadidi Branch. This study used descriptive qualitative method. Researchers will explain the data obtained through interviews, observation, documentation, so as to get answers to problems in detail and clearly. The results of this study indicate that 4 aspects of the VAT accounting treatment at PT Daya Anugrah Mandiri Airmadidi Branch are in accordance with existing tax provisions and regulations, namely recognition, calculation, presentation, and reporting. But the recording is not appropriate because there is a recording error which results in data differences.